2008
DOI: 10.1152/ajpgi.00196.2007
|View full text |Cite
|
Sign up to set email alerts
|

Increase in stretch-induced rhythmic motor activity in the diabetic rat colon is associated with loss of ICC of the submuscular plexus

Abstract: Diabetes affects many aspects of gastrointestinal motility, in part due to changes in interstitial cells of Cajal (ICC). The effect of diabetes on the colon, however, is not well characterized, and the aim of the present study was to investigate possible relationships between altered colonic motility as a consequence of streptozotocin-induced diabetes and injury to ICC. Physiological, immunohistochemical, and ultrastructural techniques were employed. The motor pattern of the rat colon was dominated by rhythmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 48 publications
5
38
0
Order By: Relevance
“…The morphological examination showed damages in the ultrastructures of the ICC. These findings were in agreement with previous findings in STZ-induced diabetic rats (9). In the previous study, ICC subtypes were examined in the colon of the STZ-induced diabetic rats; both intramuscular ICC and submuscular plexus ICC were scarce, and the area occupied by intramuscular ICC and submuscular plexus ICC was significantly lower compared with the control rats.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The morphological examination showed damages in the ultrastructures of the ICC. These findings were in agreement with previous findings in STZ-induced diabetic rats (9). In the previous study, ICC subtypes were examined in the colon of the STZ-induced diabetic rats; both intramuscular ICC and submuscular plexus ICC were scarce, and the area occupied by intramuscular ICC and submuscular plexus ICC was significantly lower compared with the control rats.…”
Section: Discussionsupporting
confidence: 91%
“…Reduction in the number of ICC has been reported in patients with diabetes (19,27) as well as in animal models of diabetes (9,15,43). The impairment in ICC was reported to be correlated with dysmotility of the gut in diabetic animals (9,43).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the current study, Western blot showed an 80% loss of interstitial cells of Cajal in the colon of diabetic rats compared with the control group, which is consistent with previous findings. 19 Our study also found that the expression of c-kit increased significantly in low-and highfrequency-stimulation-treated diabetic rats but was not altered in the sham stimulation group, suggesting that electroacupuncture, both low and high frequency, has the capability to increase the expression of c-kit in diabetic rats. This was consistent with the previous results.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have used streptozotocin (STZ) to cause specific loss of pancreatic ␤-cells creating type 1 diabetes-like animal models. STZ-induced diabetic rats have been reported to exhibit increased small intestine smooth muscle mass and increased colon contractility (10,26). The spontaneous contractile activity in STZ-induced diabetic rat colon smooth muscle was increased (12) without a change in intracellular Ca 2ϩ handling (11), while, in the ileum, intracellular Ca 2ϩ handling was decreased (11).…”
mentioning
confidence: 99%